Mensurando o emprego no setor turismo no Brasil: Do nível nacional ao regional e local - Patrícia Alessandra Morita Sakowski (Instituto de Pesquisa Econômica Aplicada (IPEA), 2015)
– This paper presents the experience of Brazil in using the administrative record rais (Annual Register on Social Information) to generate statistics for employment in the tourism industries at the subnational level. Overall data for employment in the tourism industries are presented for the national, regional and local level along with the respective maps and, as an illustrative case, comparative statistics of employment and characteristics of workers and establishments in the tourism industries are provided for Brazil, Bahia, Salvador and touristic cities in Bahia. The experience of Brazil shows that administrative records can be a rich data source from which valuable sub-national statistics for tourism can be derived in a relatively inexpensive way. It also suggests that countries with good quality administrative records could benefit from exploring these databases as an important source of employment statistics for the tourism industries.
Keywords: L83; J21; 330; tourism; employment; administrative registers; subnational statistics; regional